High-Salt Attenuates the Efficacy of Dapagliflozin in Tubular Protection by Impairing Fatty Acid Metabolism in Diabetic Kidney Disease - Zou, Meina; Chen, Yanrong; Zheng, Zongji; Sheng, Shuyue; Jia, Yijie; Wang, Xiangyu; Ren, Shijing; Yang, Yanling; Li, Xiaomin; Dong, Wenhui; Guan, Meiping; Zhang, Qian; et al. (Frontiers in Pharmacology, 2021)
High-salt intake leads to kidney damage and even limits the effectiveness of drugs. However, it is unclear whether excessive intake of salt affects renal tubular energy metabolism and the efficacy of dapagliflozin on renal function in diabetic kidney disease (DKD). In this study, we enrolled 350 DKD patients and examined the correlation between sodium level and renal function, and analyzed influencing factors. The results demonstrated that patients with macroalbuminuria have higher 24h urinary sodium levels. After establishment of type 2 diabetes mellitus model, the animals received a high-salt diet or normal-salt diet. In the presence of high-salt diet, the renal fibrosis was aggravated with fatty acid metabolism dysregulation. Furthermore, Na+/K+-ATPase expression was up-regulated in the renal tubules of diabetic mice, while the fatty acid metabolism was improved by inhibiting Na+/K+-ATPase of renal tubular epithelial cells. Of note, the administration with dapagliflozin improved renal fibrosis and enhanced fatty acid metabolism. But high salt weakened the above-mentioned renal protective effects of dapagliflozin in DKD. Similar results were recapitulated in vitro after incubating proximal tubular epithelial cells in high-glucose and high-salt medium. In conclusion, our results indicate that high salt can lead to fatty acid metabolism disorders by increasing Na+/K+-ATPase expression in the renal tubules of DKD. High salt intake diminishes the reno-protective effect of dapagliflozin in DKD.